Effects of different live feed on larval growth and development in ballan wrasse (Labrus bergylta Ascanius, 1767): - A metabolomics study - Almli, Martin (Institutt for biologi, 2012)
The use of ballan wrasse (Labrus bergylta) for the treatment of salmon lice (Lepeophtheirus samonis) in salmon farming is rapidly growing due to resistance to chemical treatments. The demand for high quality and large amounts of ballan wrasse has thus led to the development of ballan wrasse farming. Due to the small size of the newly hatched larvae, the first-feeding of the larvae has become a bottleneck area. The size and nutritional properties of the live feed chosen can greatly affect both growth and development. Using copepods as live feed in the first part of the feeding regime should give a positive effect on the larval growth and development as they are the natural prey of marine fish larvae and are nutritional superior to rotifers.The aim of this study was to use 1H-NMR to examine the differences in larval metabolic composition as a function of the different types of live feed, as well as to find the most suited method for preparation of ballan wrasse samples for metabolic analysis. To examine this, ballan wrasse larvae was fed using four different feeding regimes. The live feed used was different between the four groups for the first 30 days post hatch. After this all groups were fed the same diet. Larvae in the Copepod group were fed only the copepod Acartia tonsa. The Cop7 was fed copepods the first 7 days, then enriched rotifers. The RotMG group was fed enriched rotifers, and the RotChl group was fed unenriched rotifers. After 30 days post hatch, all treatments was fed enriched Artemia before weaning to formulated feed. Results from the present study indicate that the use of copepods in first-feeding of ballan wrasse resulted in an increase in growth compared to larvae fed rotifer diets. Metabolic analysis of the larvae show that changes in the levels of certain metabolites can be used as biomarkers for growth and development. Differences seem to be correlated to feed composition, with TMAO and taurine standing out as reliable biomarkers for growth differences